A Tapped Density Taguchi Optimization for Orange Peel Particulate Green Fillers - Ajibade, Oluwaseyi Ayodele; Agunsoye, Johnson Olumuyiwa; Oke, Sunday Ayoola (IJIEM - Indonesian Journal of Industrial Engineering and Management, 2024)
Transportation of green fillers for composites has serious densification implications due to particulate shape irregularities and size distributions. To date, few scientific studies are available on the tapped density measurements of orange peel particulate fillers. In this work, experiments were conducted on the tapped density of orange peel particulates in gentle and successive taps to the measuring cylinder containing the particulate matter. Taguchi's technique of "smaller-the-better" quality characteristics used in measuring the signal-to-noise (S/N) ratio was applied to determine the optimal setting of the tapped density process parameters. Within a range of taps from 1 to 48 points, all tapped points showed that 0.425mm OPP has a higher average apparent density of 3.22g/cm2 than 0.600mm (i.e. 3.189g/cm3) except for points at 8, 28 and 32 taps. Furthermore, for the 0.600mm OPP, its average tapped density improved by 6.97% compared to its average apparent density. Moreover, it was found that the Taguchi optimal setting for the tapped density of OPP given was A1B1C1, which reads as 8.727 number of taps, a tapped density of 4.433 and 4.395g/cm3, respectively, for the 0.425 and 0.600mm OPP samples sizes. This means that the required number of taps to obtain OPPs with light density and structural integrity to meet improved composite variety demands would be 8.727 taps, while a tapped density of 4.433 and 4.395g/cm3 is required for the 0.425 and 0.600mm OPP sizes. Hence, the number of taps was the tapped density parameter that had the greatest effect on the S/N ratios of the tapped filler materials. The results are of immense benefit to composite design engineers and equipment manufacturers for behavioural simulation and testing purposes.